Recovery of kicking kinematics and performance following repeated high-intensity running bouts in the heat: Can a rapid local cooling intervention help young soccer players? - Palucci Vieira, L. H.; Carling, C.; Kalva-Filho, C. A.; Santinelli, F. B.; Velluto, L. A. G.; da Silva, J. P.; Clemente, F. M.; Kellis, E.; Barbieri, F. A. (Journal of Sports Sciences, 2023)
The effects of a cooling strategy following repeated high-intensity running (RHIR) on soccer kicking performance in a hot environment (>30ºC) were investigated in youth soccer players. Fifteen academy under-17 players participated. In Experiment 1, players completed an all-out RHIR protocol (10×30 m, with 30s intervals). In Experiment 2 (cross-over design), participants performed this running protocol under two conditions: (1) following RHIR 5 minutes of cooling where ice packs were applied to the quadriceps/hamstrings, (2) a control condition involving passive resting. Perceptual measures [ratings of perceived exertion (RPE), pain and recovery], thigh temperature and kick-derived video three-dimensional kinematics (lower limb) and performance (ball speed and two-dimensional placement indices) were collected at baseline, post-exercise and intervention. In Experiment 1, RHIR led to small-to-large impairments (p < 0.03;d = -0.42--1.83) across perceptual, kinematic and performance measures. In experiment 2, RPE (p < 0.01; Kendall`s W = 0.30) and mean radial error (p = 0.057; ?2 = 0.234) increased only post-control. Significant small declines in ball speed were also observed post-control (p < 0.05; d = 0.35). Post-intervention foot centre-of-mass velocity was moderately faster in the cooling compared to control condition (p = 0.04; d = 0.60). In youth soccer players, a short cooling period was beneficial in counteracting declines in kicking performance, in particular ball placement, following intense running activity in the heat.